Research on digital finance, financial regulation and commercial bank risk-taking - Wang, Ruixue; Cui, Wenyi (Economics & Management Review, 2024)
This paper selects the data of 160 commercial banks in China from 2015 to 2023, and empirically analyzes the impacts and mechanisms of digital finance and financial regulation on commercial banks’ risk-taking by using a systematic GMM model. It is found that digital finance increases the level of commercial bank risk-taking, and the effect is more significant for smaller banks. In addition, increasing the intensity of financial regulation inhibits the effect of digital finance on the level of commercial bank risk-taking. The findings of this paper have certain reference value for commercial banks in the context of the rapid development of digital finance how to more effective risk management and financial regulators how to better prevent and control systemic risk, commercial banks should continue to enhance their own competitiveness, and financial regulators should maintain the sound operation of the banking industry to prevent the occurrence of systemic risk.